«De Naples… à la Sicile». Excursus on travels in Southern Italy by François Debret (1777-1850) - Alessio Mazza (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
The essay explores the journeys undertaken in Italy by the Parisian architect François Debret between 1806 and 1808 and probably between 1827 and 1830, focusing on the volumes dedicated to Southern Italy of the Fund Voyages en Italie, preserved at the Library of the École Nationale Supérieure des Beaux-Arts in Paris. This collection retains handwritten pages, drawings, architectural reliefs, sketches, notes, prints, engravings, maps, press cuttings and various documents; from the analysis of this corpus of documents, currently relatively unknown, emerges the attention of Debret as much for the classical architectures and the archaeological emergencies, as for simple civil buildings or rural architectures, without neglecting the landscape, uses and popular costumes, depicted in 30 colored engravings collected in a recently attributed album, kept in the National Library of Paris. Debret returns an admired vision of Southern Italy, powered by the passionate curiosity of a scholar-traveler who, with a great desire for knowledge, goes in search of ideas and inspirations for his own professional activity and memories to preserved forever.